2019
DOI: 10.1002/cncr.32397
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for older adults with acute myeloid leukemia after an intensive care unit admission

Abstract: BACKGROUND: Older adults with acute myeloid leukemia (AML) are often assumed to have poor outcomes after admission to the intensive care unit (ICU). However, little is known about ICU utilization and post-ICU outcomes in this population. METHODS: The authors conducted a retrospective analysis for 330 patients who were 60 years old or older and were diagnosed with AML between 2005 and 2013 at 2 hospitals in Boston.They used descriptive statistics to examine the proportion of patients admitted to the ICU as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“… 52 During treatment, especially within the first few months following diagnosis, older patients often experience serious toxicities requiring hospitalization. 53 Impairments in geriatric assessment domains further complicate the course of treatment. Patients with impairments are at higher risk of treatment-related toxicities that require treatment delays or discontinuation, which can compromise survival.…”
Section: Discussionmentioning
confidence: 99%
“… 52 During treatment, especially within the first few months following diagnosis, older patients often experience serious toxicities requiring hospitalization. 53 Impairments in geriatric assessment domains further complicate the course of treatment. Patients with impairments are at higher risk of treatment-related toxicities that require treatment delays or discontinuation, which can compromise survival.…”
Section: Discussionmentioning
confidence: 99%
“…In older patients, age-related frailties and social conditions pose further challenges concerning QoL and health care. Published data showed that older patients with AML spend 28% of their time in the hospital and 14% attending outpatient clinic appointments [219]; in addition, almost one-third are admitted to the intensive care unit at diagnosis or after subsequent treatments [220]. However, even if patients with aggressive hematologic malignancies have high symptom burden and impaired QoL comparable to those of solid tumor patients [221,222], the use of palliative care services is less frequent in hematologic settings [223].…”
Section: Quality Of Life and Palliative Carementioning
confidence: 99%
“…Patients receiving the best supportive care alone for AML spend 25–30% of their time in hospital and approximately 15% of their time attending clinic appointments [ 154 ]. Many of them have a high symptom burden [ 155 ], and one third of them are admitted to intensive care units during their initial symptoms [ 156 ]. Similar observations were also made in a third study; a significant proportion of elderly/unfit patients spend a significant part of their last days of life in hospital [ 157 ].…”
Section: Quality Of Life For Aml Patientsmentioning
confidence: 99%